2004
DOI: 10.1111/j.0300-9475.2004.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Active Synthesis of Mouse Polymeric Immunoglobulin Receptor in the Epithelial Cells of the Distal Urinary Tubule in Kidney

Abstract: The tissue distribution of mouse polymeric immunoglobulin receptor (pIgR) has been demonstrated. By Northern blot hybridization, pIgR mRNA expression was detected in liver, intestine, stomach, lung and kidney. A weak expression was also detected in thymus by reverse transcriptase-polymerase chain reaction. The pIgR expression in kidney was further studied and confirmed that pIgR protein was actively synthesized in the epithelial cells of distal urinary tubule and of Henle's loop. Immunoelectron microscopical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
4
10
0
Order By: Relevance
“…In control kidneys, pIgR expression is low or absent in most tubules, except for occasional cells in D. biflorus agglutinin-negative tubules (Fig. 1C), consistent with a previous report (19).…”
Section: Pigr Is Expressed In Renal Cyst-lining Cells and Processedsupporting
confidence: 92%
See 2 more Smart Citations
“…In control kidneys, pIgR expression is low or absent in most tubules, except for occasional cells in D. biflorus agglutinin-negative tubules (Fig. 1C), consistent with a previous report (19).…”
Section: Pigr Is Expressed In Renal Cyst-lining Cells and Processedsupporting
confidence: 92%
“…RNA (2 g) was converted to cDNA using Moloney murine leukemia virus reverse transcriptase reverse transcriptase (Promega Corp., Madison, WI). The following primers were used for qPCR amplification: ms pIgR, 5Ј-gccaaaccttgaggtgacg-3Ј (forward) and 5Ј-taccagccttcatcttccttactgaccggg-3Ј (reverse) (19); crossspecies ␤-actin, 5Ј-gaagtgtgacgttgacatcc-3Ј (forward) and 5Ј-acagagtacttgcgctcagg-3Ј (reverse) (26). The amplification program included an annealing temperature of 55°C and used GoTaq qPCR Master Mix (Promega) and the Stratagene Mx3000P qPCR system (Agilent Technologies, Inc., Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of pIgR protein seems to be similar to that of the normal rat kidney, in which we have demonstrated that pIgR protein is preferentially expressed near the luminal surface of the thick ascending limb and throughout some proximal tubules (11). The decreased pIgR staining in the cortical tubules of the P(ϩ) E. coli-infected mice suggests that pIgR protein is depleted from the apical storage vesicles of the renal epithelia, where it has been shown clearly to be stored by electron microscopy in normal mice (33), and is consistent with our findings of decreased pIgR protein levels by Western blot in the P(ϩ) E. coli-infected group at 48 h. Hence, the depletion of pIgR protein in the kidney cortex of pyelonephritis animals at 48 h (Figure 4) results from the combined effects of decreased pIgR RNA levels ( Figure 2) and the continued excretion of SC (cleaved fragment of pIgR) either attached to IgA ( Figure 5) or as FSC.…”
Section: E Coli Expressing P Fimbriae Decrease Pigr Protein Levels Isupporting
confidence: 68%
“…We and others have localized pIgR protein in the mouse kidney (32,33). We are the first to demonstrate that infection caused by P(ϩ) E. coli decreases pIgR expression in the cortical nephron segments.…”
Section: E Coli Expressing P Fimbriae Decrease Pigr Protein Levels Imentioning
confidence: 62%